Desmundo, de Ana Miranda: a (des)leitura de um Brasil pela voz ficcional da mulher - Holanda, Camila Vilela de (2019)
The present research aims to analyze the Brazilian writer Ana Miranda’s novel Desmundo (1996), by the means of the female characters’ voices, especially the protagonist’s one – a young woman called Oribela. Written in the form of a diary, the literary work embraces the narrative of a girl who lands in Brazil in 1555, coming from Portugal in a ship, due to the order of the Queen. Oribela faces the paradoxes between the reality of having been educated in a Portuguese convent and the savagery of a country with no identity, morality nor even been a nation. This research proposes to search the ways, on giving voice to a female character – who has traditionally been excluded from the official accounts of our History – Ana Miranda is able to develop a critical reading of the contemporary reality under the lens of the Historical Novel as theoritized by György Lukács, the Linda Hutcheon’s Historiographic Metafiction and Mary Del Priore historical role of women in colonial Brazil